2004
DOI: 10.1203/01.pdr.0000142711.24999.8a
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin Concentrations in Newborn Infants in Early Postnatal Life

Abstract: Serum adiponectin levels were investigated in 28 small-forgestational-age (SGA) and 34 appropriate-for-gestational-age (AGA) term neonates to examine how fetal growth correlates with adiponectin levels. A blood sample for determination of adiponectin was obtained during the first 24 h of life. The levels of serum adiponectin were significantly higher in all newborn infants than in healthy children (28.7 Ϯ 17.0 versus 9.3 Ϯ 6.1 g/mL; p Ͻ 0.01). There was a significant difference in adiponectin levels between SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 36 publications
8
54
4
2
Order By: Relevance
“…In adults, adiponectin concentration is inversely related to adiposity, but its association with adiposity is poorly understood (9,11,13). Some studies indicate a positive correlation between cord plasma adiponectin concentration and adiposity in infants (8,12,14,(16)(17)(18)(19)(20) and some have found no significant correlation (9,15).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%
“…In adults, adiponectin concentration is inversely related to adiposity, but its association with adiposity is poorly understood (9,11,13). Some studies indicate a positive correlation between cord plasma adiponectin concentration and adiposity in infants (8,12,14,(16)(17)(18)(19)(20) and some have found no significant correlation (9,15).…”
Section: G Estational Diabetes Mellitus (Gdm) Is Impairedmentioning
confidence: 99%
“…11 Recent studies have shown that cord blood adiponectin concentrations are correlated positively with birth weight, suggesting that fetal adiponectin levels are likely to influence fetal growth. 8,10,27,28 MazakiTovi et al 29 have reported that the cord blood adiponectin concentration in the smaller neonate of discordant twins is lower than that in the larger counterpart.…”
Section: Adiponectin Snps and Cord Blood Adiponectin M Saito Et Almentioning
confidence: 99%
“…Furthermore, we confirmed previous findings of no gender difference in adiponectin levels. 8,10,11,28 Serum adiponectin levels are known to be inversely correlated with body fat mass in adolescents and adults, whereas cord blood adiponectin concentrations are positively correlated with birth weight s.d. score, mostly determined by fat mass.…”
Section: Adiponectin Snps and Cord Blood Adiponectin M Saito Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier work, this research team demonstrated that serum adiponectin levels in the first day of life were significantly higher in AGA neonates than in those born with small for gestational age (SGA) birth weight. 6 These previous data likely reinforced the potential role of adiponectin in prenatal growth. On the other hand, it is also possible that the lower levels of adiponectin found in SGA neonates as observed in that study are just a consequence of fetal growth impairment.…”
mentioning
confidence: 68%